Development of Face Mask Detection System Using Arduino Alert Feature - Thangaveloo, Siveshwarn; Mohd.Yasin, Suhaila (Applied Information Technology And Computer Science, 2023)
Coronavirus Disease 2019 (COVID-19) has emerged as a serious public health issue, causing severe acute respiratory illness in humans. The limited availaibility of pharmaceutical interventions for the COVID 19 outbreak has compelled governments all over the world to impose precautions and hygienic measures to prevent virus transmission. One of these important measures is wearing a face mask in public places, which significantly reduces the risk of transmission. Hence, a system for monitoring face mask detection using a machine learning model is developed. The system is developed to (state the objectives here). Using the Iterative Design Model, the system incorporates Arduino alert feature to alert faces that are captured by the camera with the absence of a face mask. Python programming language is used in the system development. Subsequently, the system is then tested to a selected group of user to determine its applicability.